A revision of Ceranota Stephens, subgenus of Aleochara Gravenhorst (Coleoptera: Staphylinidae: Aleocharinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2009)
Types and additional material of the species of the Aleochara subgenus Ceranota Stephens, 1839 are revised. In all, 30 species are recognised, including four species of doubtful status, whose type material is either lost or inaccessible, or whose male sexual characters are unknown. The known distribution of the subgenus is confined to the Western Palaearctic region, eastwards to Afghanistan. Diagnoses of the subgenus, as well as of the individual species are provided. The following synonymies are proposed: Aleochara penicillata Peyerimhoff, 1901 = A. caprae Gridelli, 1922, syn. n. = A. meschniggi Bernhauer, 1943, syn. n.; A. strasseri Bernhauer, 1901 = A. matzenaueri Rambousek, 1907, syn. n. Aleochara conviva Eppelsheim, 1878, previously a synonym of A. lurida Motschulsky, 1860, and A. consors Eppelsheim, 1890, previously a synonym of A. adusta Eppelsheim, 1890, are revalidated. Aleochara tuberiventris Kraatz, 1859 is excluded from the subgenus. Neotypes are designated for Aleochara ruficornis Gravenhorst, 1802, A. erythroptera Gravenhorst, 1806, A. major Fairmaire, 1858, A. caprae Gridelli, 1922, and A. matzenaueri Rambousek, 1907. Lectotypes are designated for Aleochara diversicollis Fauvel, 1900, A. melichari (Reitter, 1889), A. meschniggi Bernhauer, 1943, A. opacina Fauvel, 1900, A. adusta Eppelsheim, 1890, A. consors Eppelsheim, 1890, and A. libanica Eppelsheim, 1889. Four species are described and illustrated for the first time: Aleochara (Ceranota) virilis sp. n. (Russia: Adygeya), A. (C.) claviculata sp. n. (NE-Turkey), A. (C.) sarica sp. n. (Iran: Mazandaran), and A. (C.) feldmanni sp. n. (Afghanistan). Zoogeographic and bionomic data are compiled. Additional records of Ceranota species are reported, among them numerous new country records. The distributions of eight species are mapped. A key to species and a catalogue are provided.KeywordsStaphylinidae, Aleocharinae, Aleochara, Ceranota, Palaearctic region, taxonomy, new species, revalidation, new synonymies, descriptions, redescriptions, neotype designations, lectotype designations, distribution, new records.Nomenclatural Actslurida Motschulsky, 1860 (Aleochara), Lectotype now a synonym of Aleochara (Ceranota) subtumida (Hochhuth, 1849)tuberiventris Kraatz, 1859 (Aleochara), Lectotype; stat. rev. excluded from the subgenus Ceranotaadusta Eppelsheim, 1890 (Aleochara (Ceranota)), Lectotypecaprae Gridelli, 1922 (Aleochara (Ceranota)), Neotype; syn. n. of Aleochara (Ceranota) penicillata Peyerimhoff, 1901claviculata Assing, 2009 (Aleochara (Ceranota)), spec. n.consors Eppelsheim, 1890 (Aleochara (Ceranota)), Lectotype; stat. rev. hitherto ba synonym of Aleochara (Ceranota) adusta Eppelsheim, 1890conviva Eppelsheim, 1878 (Aleochara (Ceranota)), stat. rev. hitherto a synonym of Aleochara (Ceranota) lurida Motschulsky, 1860diversicollis Fauvel, 1900 (Aleochara (Ceranota)), Lectotypeerythroptera Gravenhorst, 1806 (Aleochara (Ceranota)), Neotypefeldmanni Assing, 2009 (Aleochara (Ceranota)), spec. n.libanica Eppelsheim, 1889 (Aleochara (Ceranota)), Lectotypemajor Fairmaire, 1858 (Aleochara (Ceranota)), Neotypematzenaueri Rambousek, 1907 (Aleochara (Ceranota)), Neotype; syn. n. of Aleochara (Ceranota) strasseri Bernhauer, 1901melichari (Reitter, 1889) (Aleochara (Ceranota)), Lectotype described as Ceranota melicharimeschniggi Bernhauer, 1943 (Aleochara (Ceranota)), Lectotype; syn. n. of Aleochara (Ceranota) penicillata Peyerimhoff, 1901opacina Fauvel, 1900 (Aleochara (Ceranota)), Lectotyperuficornis Gravenhorst, 1802 (Aleochara (Ceranota)), Neotypesarica Assing, 2009 (Aleochara (Ceranota)), spec. n.virilis Assing, 2009 (Aleochara (Ceranota)), spec. n.